IDENTIFIKASI KARAKTERISTIK SENSORI DAN FISIKOKIMIA KEFIR AIR KELAPA TUA (Cocos nucifera L.) - Anggun Sri Mulyani Sagala; Caca Pratiwi; Esi Emilia; Risti Rosmiati; Hardi Firmansyah (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
Kefir is a probiotic drink that can be produced from dairy and non-dairy ingredients. Old coconut water (Cocos nucifera L.), which is often discarded as waste, can be used as a raw material for kefir production because it still has potential nutritional value for fermentation media. This study aims to identify the sensory and physicochemical characteristics of kefir made from old coconut water. This study used a completely randomized design (CRD) with starter concentration treatments consisting of two levels, namely 5% and 10% starter concentration, each conducted with two replicates. The parameters observed were sensory parameters, including color, aroma, taste, viscosity, and soda sensation, while physicochemical parameters included pH, viscosity, total dissolved solids, alcohol, protein, fat, ash, total sugar, and carbohydrates. Sensory evaluation showed that kefir made from old coconut water with a starter concentration of 5% had a higher acceptance level among panelists. Furthermore, the physicochemical characteristics of aged coconut water kefir at starter concentrations of 5% and 10% showed a pH ranging from 4.13 to 4.47, viscosity of 38.6 to 39.0 mP.s, total dissolved solids of 9.3 to 9.8°Brix, alcohol content of 4.16 to 4.95%, protein content of 0.35-0.38%, fat content of 0.58-2.17%, ash content of 0.19-0.27%, total sugar content of 4.15%-5.27%, and carbohydrate content of 3.74-4.74%. This study provides an overview of the sensory and physicochemical characteristics of kefir made from aged coconut water as a non-dairy fermentation medium.